2018
DOI: 10.2174/1389450119666180219120534
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-IKKβ Pathway as a Target for Drug Development: Realities, Challenges and Perspectives

Abstract: Although only proteasome inhibitors, such as bortezomib and carfilzomib, are a reality as therapeutically useful drugs among the known modulators of possible targets in the NF-κB-IKKβ pathway, some other prototypes described as IKKβ inhibitors have entered clinical stages as drug candidates for the control of inflammatory diseases. It is important to note that some classical drugs available on the pharmaceutical market, such as acetylsalicylic acid, were also described more recently as NF-κB pathway modulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 0 publications
4
31
0
Order By: Relevance
“…Since the ubiquitination of IκB by the SCF-B-TrCP ubiquitin ligase complex and the subsequent degradation by the 26S proteasome is a crucial step in the NF-κB activation pathways, preventing the degradation of IκBα is a potential method of treatment to prevent NF-κB activation [ 13 , 14 , 141 , 155 , 156 ].…”
Section: Inhibitors Of Nf-κb Function and Selected Pharmacologicalmentioning
confidence: 99%
“…Since the ubiquitination of IκB by the SCF-B-TrCP ubiquitin ligase complex and the subsequent degradation by the 26S proteasome is a crucial step in the NF-κB activation pathways, preventing the degradation of IκBα is a potential method of treatment to prevent NF-κB activation [ 13 , 14 , 141 , 155 , 156 ].…”
Section: Inhibitors Of Nf-κb Function and Selected Pharmacologicalmentioning
confidence: 99%
“…NF-kB family members are responsible for up-regulating dozens of genes including those expressing the pro-inflammatory cytokines, chemokines, immuno-receptors, cell adhesion molecules and microRNAs [ 1 6 , 59 62 ]. Because of this NF-kB signaling is often a central mediator of the immune and inflammatory response; its activation represents the common endpoint of a series of signal transduction events initiated by a vast array of stimuli related to many biological processes such as apoptosis, cell growth, differentiation, innate-immunity, inflammation, tumor cell growth and the presence of ROS generated by neurotoxic metals in the environment [ 59 , 60 ]. NF-kB (p50/p65) dimeric complexes are typically held in the cytoplasm in an inactive state complexed with an NF-kB inhibitor (I-kappa-B; IkB) protein; IkB is next typically phosphorylated by IkB kinases (IKKs) in response to different activators such as ROS from different sources and is subsequently degraded, thus liberating an active NF-kB (p50/p65) complex.…”
Section: Discussionmentioning
confidence: 99%
“…These next translocate to the nucleoplasm where they recognize and bind to NF-kB features of DNA, typically in the upstream promoter DNA and activate large numbers of NF-kB-sensitive genes [ 1 6 , 59 62 ]. The 551-amino acid NF-kB p65 subunit, also known as RELA or NFKB3, is encoded from a 1473 nucleotide gene located on human chr 1q13 and contains a N-terminal REL-homology domain (RHD) and a C-terminal transactivation domain (TAD); the RHD is involved in the actual DNA binding, dimerization and NF-κB/REL inhibitor interaction [ 1 , 2 , 59 , 60 ]. NF-kB p65 (RELA) is expressed alongside NF-kB p50 in various cell types, including epithelial, endothelial and neuronal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as a disruption of homeostasis in NF-jB signaling also results in the consequent various activation/ deactivation of pathways, the expectations may have to be toned down, especially as it has been shown that some classical drugs may act as NF-jB modulators or IKKb inhibitors [404]. For example, the compound salvianolic acid C (SalC) isolated from the plant, Salvia miltiorrhiza Bunge, can inhibit "LPS-induced inflammatory response and NF-jB activation through the activation of AMPK/Nrf2 signaling both in vivo and in vitro" [405].…”
Section: Caffeic Acid Phenethyl Ester (Cape)mentioning
confidence: 99%